Integration of Learning Cycle Stage with Inquiry Labs Method in Learning Physics to Improve Cognitive Ability and Science Process Skills of High School Student - Diki Rukmana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
One of the goals of the development of the 2013 curriculum is the change of the learning process (from students to be learned to students to find out) by focusing on improving cognitive and skills. The fact shows that the process of physics learning in high school is still not fully in accordance with the principles of applying the curriculum 2013 so that the impact on the low achievement of cognitive abilities and students' science process skills. Based on these problems, a pre-experiment research was conducted using a one-pretest-posttest research design that aims to obtain an overview of cognitive skills improvement and students' science process skills as the impact of integrated learning cycle stages with inquiry labs method in physics learning. The results showed that there was an increase in cognitive abilities and science process skills of students with N-gain of 0.57 and 0.69.